ADAM9 Mediates Triple-Negative Breast Cancer Progression via AKT/NF-κB Pathway - Zhou, Rui; Cho, William C. S.; Ma, Victor; Cheuk, Wah; So, Yik-Ka; Wong, S. C. Cesar; Zhang, Mingrong; Li, Cong; Sun, Yujie; Zhang, Hong; Chan, Lawrence W. C.; Tian, Mei (Frontiers in Medicine, 2020)
Upregulation of a disintegrin and metalloprotease 9 (ADAM9) is correlated with progression of cancers, such as prostate, bladder and pancreatic cancers. However, its role in triple negative breast cancer (TNBC) is still unclear. Our study is aimed to investigate whether ADAM9 is upregulated and contributes to the aggressiveness in TNBC. Breast cancer cell lines and patient specimens were used to evaluate the ADAM9 expression by western blotting and immunohistochemistry staining respectively. Compared with the non-TNBC, ADAM9 expression was significantly increased in MDA-MB-231 (a TNBC cell line) cells and TNBC patient specimens. Based on the data acquired from public databases, the correlation between ADAM9 expression and breast cancer patient survival was analyzed by Kaplan-Meier method. It was shown in public data that ADAM9 overexpression was significantly correlated with poorer survival in patients with TNBC. Furthermore, ADAM9 in MDA-MB-231 cells was knocked down by small interference RNA (siRNA) and then MTT/Colony formation assay, wound healing assay and transwell invasion assay were performed to test the cell proliferation, migration and invasion respectively. We found that inhibiting ADAM9 expression suppressed MDA-MB-231 cell proliferation, migration and invasion by lowering the activation of AKT/NF-kB pathway. Our results indicated that ADAM9 is an important molecule in mediating TNBC aggressiveness and may be a useful therapeutic target in TNBC treatment.